METAPHORS AND PROBLEMS OF THEİR CLASSİFİCATİON İN MODERN WORLD LİNGUİSTİCS - Husniyya Tanriverdiyeva (Research Focus International Scientific Journal, 2024)
Metaphors are an artistic-linguistic tool that creates imagery in literary texts. In our daily life we use these tools inevitably enough. Metaphor is based on complex thought operations with an associative character. This problem was studied with great interest by Aristotle and Theophrastus in Ancient Greece under the name of tropes, and by Cicero, Hermogenes and others in Rome. When they talked about metaphors (tropes) they considered their poetic effect and their influence on the semantics of words. When talking about tropes Aristotle approached metaphors logically and saw them as manifestations of syllogisms and logical figures. The logical approach to metaphors is related to the period when rhetoric was inseparable from logic and philosophy. Ancient philosophers described the manifestations of this phenomenon which decorates speech on the basis of ancient Sanskrit poetic texts. The study of metaphors declines for a long time after the Greek and Roman phase. Approaching this issue from a purely linguistic point of view reappears as a part of poetics.